2017
DOI: 10.1186/s12957-016-1092-1
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of the postoperative ratio of C-reactive protein to albumin for complications after colorectal surgery

Abstract: BackgroundThe ratio of C-reactive protein to albumin, as a novel inflammation-based prognostic score, is associated with outcomes in cancer and septic patients. The diagnostic accuracy of the CRP/albumin ratio has not been assessed in colorectal surgery for postoperative complications.MethodsA total of 359 patients undergoing major colorectal surgery between 2012 and 2015 were eligible for this study. Uni- and multivariate analyses were performed to identify risk factors for postoperative complications. Receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 31 publications
2
31
0
Order By: Relevance
“…Merging albumin and CRP into a single index is demonstrated to be associated with poor prognosis in a variety of disorders including cancer and sepsis . We assumed that increased CRP/albumin ratio indicates a higher inflammatory state and may be superior to CRP and albumin alone in determining the prevalence and severity of CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Merging albumin and CRP into a single index is demonstrated to be associated with poor prognosis in a variety of disorders including cancer and sepsis . We assumed that increased CRP/albumin ratio indicates a higher inflammatory state and may be superior to CRP and albumin alone in determining the prevalence and severity of CAD.…”
Section: Discussionmentioning
confidence: 99%
“…For many surgeons, the early identification of SSI is still a challenge. In the period after elective colorectal surgery, SSI can lead to prolonged hospital stays, increased morbidity and [5]. Despite the combined evaluation of clinical, laboratory, and radiologic findings, early diagnosis of SSI cannot be made reliably by any known individual feature or even by experienced clinical judgment [9].…”
Section: Discussionmentioning
confidence: 99%
“…The research on CAR is still in development. Ge et al [5] found that patients with CAR >2.2 on POD3 should be monitored intensively for early detection of post-operative complications. Shibutani et al [16] found pre-operative CAR to be a useful prognostic marker in patients with colorectal cancer undergoing potentially curative surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations